English essay writing proficiency in Grade 9 at selected public schools in Gauteng in the modern era - Puleng Kubuzie; Christopher Rwodzi; Cornelia G. Smith (Reading & Writing, 2025)
Background: Despite essay writing being a highly discussed topic, a growing body of writing knowledge gathered from various approaches can inform teachers and learners about revision efforts. Emphasis is placed on the significance of error analysis in English essays, given that English is a widely used language in business, facilitating communication among diverse racial groups. This underscores the importance of developing fluency in English essay writing.